PROBLEMATIKA PENERAPAN STRATEGI PEMBELAJARAN EKSPOSITORI DALAM MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI KELAS X MADRASAH ALIYAH - Kurnia Dwi rahma (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This article aims to describe the problems encountered and analyze the solutions implemented to improve the effectiveness of learning. This study employs a qualitative approach using a case study design. Data collection techniques included observation, in-depth interviews with Islamic cultural history teachers and students, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that (1) the problems in applying expository learning strategies in Islamic cultural history classes include low active student participation, limited class time, and differences in students’ levels of understanding. (2) The solutions implemented include combining expository strategies with discussion and question-and-answer strategies, using more varied learning media, and providing continuous and optimal learning motivation to students. The conclusion of this study indicates that the challenges in implementing expository learning strategies can be minimized through the application of more varied and adaptive learning strategies tailored to the characteristics of the students.